Pemberdayaan Karang Taruna dalam Pengelolaan Sampah Plastik untuk Mewujudkan Zero Waste di Dusun Cinengah - Miliyawati, Bety; Anggraini, Ine; Suparman, Ade; Rise, Rise; Wijayanti, Freni Agustantia; Zuan R, Viola Azzura; Saptiah, Diana (MENARA RIAU, 2025)
The goal of this activity is to improve the knowledge and skills of youth organizations (Karung Taruna) members in managing plastic waste so that it has utility and benefits. The approach used was to provide education by sharing good practices through community-based waste management seminars and providing training in making bricks from plastic waste and skills in making plastic handicrafts. The results of this activity were an increase in the knowledge of youth organizations (Karung Taruna) about plastic waste management and the ability to independently process waste into products that have utility and benefits.